Associations of types of dairy consumption with adiposity: cross-sectional findings from over 12 000 adults in the Fenland Study, UK. Issue 8 (28th October 2019) - Trichia, Eirini; Imamura, Fumiaki; Brage, Søren; De Lucia Rolfe, Emanuella; Griffin, Simon J.; Wareham, Nicholas J.; Forouhi, Nita G.
Abstract: Evidence from randomised controlled trials supports beneficial effects of total dairy products on body weight, fat and lean mass, but evidence on associations of dairy types with distributions of body fat and lean mass is limited. We aimed to investigate associations of total and different types of dairy products with markers of adiposity, and body fat and lean mass distribution. We evaluated cross-sectional data from 12 065 adults aged 30–65 years recruited to the Fenland Study between 2005 and 2015 in Cambridgeshire, UK. Diet was assessed with an FFQ. We estimated regression coefficients (or percentage differences) and their 95 % CI using multiple linear regression models. The medians of milk, yogurt and cheese consumption were 293 (interquartile range (IQR) 146–439), 35·3 (IQR 8·8–71·8) and 14·6 (IQR 4·8–26·9) g/d, respectively. Low-fat dairy consumption was inversely associated with visceral:subcutaneous fat ratio estimated with dual-energy X-ray absorptiometry (–2·58 % (95 % CI –3·91, –1·23 %) per serving/d). Habitual consumption per serving/d (200 g) of milk was associated with 0·33 (95 % CI 0·19, 0·46) kg higher lean mass. Other associations were not significant after false discovery correction. Our findings suggest that the influence of milk consumption on lean mass and of low-fat dairy consumption on fat mass distribution may be potential pathways for the link between dairy consumption and metabolic risk. Our cross-sectional findings warrant further research in prospective and experimental studies in diverse populations.